2022
DOI: 10.3390/metabo12060522
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cord Blood Lipids with Childhood Adiposity at the Age of Three Years: A Prospective Birth Cohort Study

Abstract: We aimed to examine the associations between cord blood lipids and childhood adiposity and to investigate whether these associations vary across birth weight categories (small for gestational age (SGA), appropriate for gestational age (AGA) and large for gestational age (LGA)) in 1306 infants in the Born in Guangzhou Cohort Study, China. Adiposity outcomes at the age of three years included z-scores of weight-for-length/height (WFLZ), body mass index (BMIZ), subscapular (SSTZ) and triceps skinfold thickness (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Our results further discovered inverse correlations between cord serum TG concentrations, TG/TC ratios and weight Z-scores and BMI Z-scores up to 18 months. These outcomes were in accordance with research work from Ye et al (19) and Cao et al (20). It has been shown that hypertriglyceridemia was closely related to islet b-cell dysfunctions, including interfered b-cell maturation, suppressed b-cell proliferation, inhibited insulin secretion, and induced insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results further discovered inverse correlations between cord serum TG concentrations, TG/TC ratios and weight Z-scores and BMI Z-scores up to 18 months. These outcomes were in accordance with research work from Ye et al (19) and Cao et al (20). It has been shown that hypertriglyceridemia was closely related to islet b-cell dysfunctions, including interfered b-cell maturation, suppressed b-cell proliferation, inhibited insulin secretion, and induced insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that cord plasma TG levels were positively associated with adiposity indicators among SGA infants but tended to be negatively associated with adiposity indicators among LGA infants in the research of Ye et al. ( 19 ). However, our outcomes did not find such opposite associations between TG levels and weight Z-scores or BMI Z-scores stratified by weight for gestational age, even after adjusting for confounding variables.…”
Section: Discussionmentioning
confidence: 95%
“…As proposed by Ye et al. ( 48 ), this potential interaction between lipid particles in the fetus could be critical for the fetal and neonatal metabolism, and may have a lasting impact on the metabolic health of the offspring. Cord blood markers including insulin, C-peptide and HOMA-IR were related to birth anthropometry in univariate, but not in multivariate analyses.…”
Section: Discussionmentioning
confidence: 89%
“…The findings of two previous studies in GDM showing inverse correlations between cord blood triglyceride and birth anthropometry further underline our results ( 19 , 28 ). Large molecules such as HDL cannot cross the placenta directly, but they could affect the metabolism of other lipids, depending on the concentration and presence ( 47 , 48 ). As proposed by Ye et al.…”
Section: Discussionmentioning
confidence: 99%